The Effect of Fishbowl-Based Concept Sentence Cooperative Models on Critical Thinking and Creativity Skills of Students - Nirfadillah Nirfadillah; Ira Irviana; Nurhayati Selvi (ETDC: Indonesian Journal of Research and Educational Review, 2026)
This research is motivated by the low critical thinking skills and creativity of elementary school students. This study aims to test the effectiveness of the implementation of the concept sentence learning model combined with the fishbowl method on improving students' critical thinking skills and creativity in natural science subjects. The method used is experimental research with a one-group pretest-posttest design involving 23 fourth-grade students at Elementary School Inpres Bira 2, Makassar. Data was gathered via questionnaires and examined utilizing paired samples tests and Wilcoxon signed ranks tests. The results showed a significant increase in the average critical thinking score from 68.86 to 88.73 (Sig. 0.000 < 0.05). Furthermore, student creativity scores increased from 51.17 to 75.08, supported by the Wilcoxon test results with an Asymp. Sig. (2-tailed) value of 0.000. The integration of these two methods effectively helps students’ structure logical concept sentences while providing a dynamic discussion space for expressing creative ideas. This research contributes an alternative active learning strategy for educators to create a more dynamic and solution-oriented classroom atmosphere.